Cryptophthalmos Syndrome: A Case Report - Anwar Ul-Haq Ahmad, Jawad Bin Yamin Butt, Tariq Mehmood Qureshi, Muhammad Tariq Khan (Pakistan Journal of Ophthalmology, 2018)
A 20 days female baby presented to us in OPD. She was the 4th child of normal parents with 3 normal siblings. She exhibited few features of cryptophthalmos which fit the criteria of Fraser syndrome. Key words: Cryptophthalmos, Fraser syndrome, Eye lid defect.